Jan Bielski’s Polemics with Stanislaw Konarski - Mieszek, Małgorzata (Piśmiennictwo zakonne w dobie staropolskiej, 2013)
The paper’s subject is the analysis of the „Preface to the Reader” by Jan Bielski. Bielski’s preface wascreated in response to the words of Stanisław Konarski (from the argument to his “Otto tragedy”). Thearticle focuses on polemical plots and on Bielski’s arguments to justify the ban on the presence of womenin Jesuit plays. Bielski’s response is being analysed in the reference to a wider background of Jesuit dramaturgyin the 18th century.